Legal Protection of MSMEs in the Digital Technology Era in Makassar City: Facing Recession - Nurhaedah, Nurhaedah; Azis, Dian Eka Puspita (Indonesia Media Law Review, 2025)
This study aims to encourage government policies and regulations in protecting MSMEs, to analyze the obstacles faced by micro, small, and medium enterprises in obtaining legality and access to the market. Using a normative-empirical legal approach method, this study examines the applicable laws and regulations and explores the socio-economic conditions of MSME actors in Makassar. The results of the study show that although the government has issued policies such as NIB, IUMK, and PIRT, the level of ownership of legal documents among MSMEs is very low. This is due to the lack of socialization, minimal digital-based knowledge services for business actors, and limited access to legal services. The digital era has  made a positive contribution to legal protection of businesses, through the Online Single Submission (OSS) system, which facilitates the creation of documents as business legalization. The use of electronic documents can strengthen legal certainty, as valid evidence if a business dispute. Therefore, intensive and continuous legal assistance is needed to increase the awareness and presence of business actors, in order to support the desires and competitiveness of the emerging MSMEs in the era of globalization and the threat of future recession.